Doubly Real: Game Studies and Literary Anthropology; or, Why We Play Games - Schweighauser, Philipp (Eludamos: Journal for Computer Game Culture, 2009)
Few game studies scholars will regret that the infelicitous ludology vs. narratology debate has been left behind. However, one misconception concerning the nature of literary theory continues to haunt game studies. If Gonzalo Frasca (correctly) observes that "Ludologists Love Stories, Too" (2003), I wish to point out that his conciliatory gesture seriously threatens to distort the concerns of literary theorists in ways that make their reflections on human sense-making indeed seem of very limited use to game studies scholars. If we truly want to know in what respects game studies can profit from literary theory without jeoparidizing the strategies of distinction a still emergent field such as game studies needs to position itself vis-à-vis dominant theoretical paradigms–and which Espen J. Aarseth calls for in his editorial to the first issue of Game Studies (2001)–we need to be aware of two things. First, narratologists make up only a fraction of the literary-theoretical community. And the narratologists most often cited by game studies scholars usually practice a structuralist version of narratology that has come under sustained critical scrutiny since the late 1960s. Second, not all literary scholars are concerned with narrative. Of course, they often study narrative texts such as novels and short stories, but they also study plays, poems, and other non-narrative texts. More importantly, even when they do study narrative texts, literary scholars–be they narratologists or not–are not always interested in the forms and functions of stories. This essay argues that game studies can profit from reflections on issues other than narrative by a literary theorist whose work has been unduly reduced to those concerns. In Cybertext: Perspectives on Ergodic Literature (1997), Aarseth refers to the work of Wolfgang Iser as one influential model of literary communication that does not help explain the specific forms and functions of nonlinear, multicursal computer games. More specifically, Aarseth argues that Iser’s notion of Leerstellen (blanks) cannot account for the kinds of openings cybertexts offer their users. Yet the later work of Iser is a much more promising avenue of exploration for ludologists. Iser’s The Fictive and the Imaginary: Charting Literary Anthropology (1993) develops what is arguably the most sustained theory of fictionality available today. While honed in the study of literary texts, Iser’s theory can tell us much about the cultural work of fiction in a variety of media without leveling the distinctions between different cultural practices. As such, Iser’s later work does not provide yet another framework for reading games as stories but challenges games studies scholars to rethink some of their central concepts, in particular ’play,’ ’simulation,’ and ’immersion.’ Moreover, it invites us to ask whether the rhetoric of distinction that much game studies scholarship still employs to stake out its claims has outlived its usefulness, serving less as an effective defense mechanism than as an obstacle to cross-disciplinary fertilization.